TYPES OF HEDONISM ON THE MAIN CHARACTER SIR WALTER ELLIOT IN THE NOVEL PERSUASION BY JANE AUSTEN - Valufi, Enggin; Astuti, Retno Budi (Universitas Gunadarma, 2020)
Hedonism is a view of life in philosophy that seeks to avoid pain and make pleasure as the main goal in life. People who embrace hedonism tend to over-pursue pleasure. The hedonism lifestyle is mostly carried out by 18th century people especially the nobles who live in high culture. They are as close to hedonism as they are in the Persuasion novel by Jane Austen. Sir Walter Elliot the main character is a nobleman who did a lot of hedonism. Hedonism which is seen as too glorifying personal pleasure to ignore others. The purpose of this study was to find out the types of hedonism done by Sir Walter Elliot in Persuasion. This research uses descriptive qualitative method because all data are in the form of sentences. The researcher uses a philosophical approach and analyzes data using Weijers' theory as the main theory. The results of this study found that Sir Walter Elliot performed two types of hedonism, namely aesthetic hedonism and selfish hedonism.